Imagined enemies China prepares for uncertain war - Lewis, John Wilson; Xue, Litai (Stanford University Press, 2006)
This is the fourth and final volume in a pioneering series on the Chinese military. The book begins with an examination of Chinese military culture and history - with special attention to the transition from Mao Zedong's revolutionary doctrine and the conflict with Moscow - and culminates with Beijing's current preoccupation with Taiwanese separatism and preparations for a war to thwart it. Because such a war might involve the United States, the Chinese have concentrated on measures to deter American intervention.